Fizika o‗qitishda talabalarning ijodiy qobiliyatlarini rivojlantirish - Matjanov, N.S (SCIENCE and SOCIETY, 2023)
The article describes the peculiarity of the development of students' creative abilities in the process of teaching phys- ics. Information is also given about interactive methods (case studies, problem-based learning) that ensure the development of students' creative abilities.
Keywords: creativity; student; teacher; activity; competence; self-study; case study; problem-based learning; physics; educational process